A great resource that should be utilised more, but also a place of anxiety: student perspectives on using an online discussion forum. (3rd July 2022) - Griffin, Lynda; Roy, James
ABSTRACT: A range of studies into the efficacy of online discussion forums is available, and this study seeks to add to the body of evidence around students' experiences of using online discussion forums within a distance learning context. The Open University (OU) is still the UK's largest provider of distance higher education. OU distance learners are encouraged to participate in asynchronous online discussion forums and collaborate with their peers, thus benefiting from working with others and reducing social distance. We investigated student perspectives on their feelings about participation in 'tutor group' forums. We drew on comments provided via email to identify key themes and provide insights into positive and negative experiences; some findings reinforce existing research, e.g. forums as a welcome source of peer and tutor support. However, we also identified practices and factors reported as causing anxiety or reluctance to enter an online 'space', and leading to non-participation. These included the nature of other students' posts, dominance by peers, unwelcome demands on students' time and the 'exposure of the self' through writing online. We consider the tensions and anxiety reported, discuss the implications, and suggest ways to improve the online student experience.